Mapping an undergraduate medical education curriculum against national and international palliative care reference learning objectives - Murphy, Rebekah; Barnes, Christopher J.; Enright, Paula D.; Gratton, Valerie; Bush, Shirley H. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background The teaching of palliative care competencies is an essential component of undergraduate medical education. There is significant variance in the palliative care content delivered in undergraduate medical curricula, revealing the utility of reference standards to guide curricular development and assessment. To evaluate our university’s undergraduate palliative care teaching, we undertook a curriculum mapping exercise, comparing official learning objectives to the national Educating Future Physicians in Palliative and End-of-Life Care (EFPPEC) and the international Palliative Education Assessment Tool (PEAT) reference objectives. Methods Multiple assessors independently compared our university’s UGME learning objectives with EFPPEC and PEAT reference objectives to determine the degree-of-coverage. Visual curriculum maps were created to depict in which part of the curriculum each objective is delivered and by which medical specialty. Results Of 122 EFPPEC objectives, 55 (45.1%) were covered fully, 42 (34.4%) were covered partially, and 25 (20.5%) were not covered by university objectives. Of 89 PEAT objectives, 40 (44.9%) were covered fully, 35 (39.3%) were covered partially, and 14 (15.7%) were not covered by university objectives. Conclusions The majority of EFPPEC and PEAT reference objectives are fully or partially covered in our university’s undergraduate medical curriculum. Our approach could serve as a guide for others who endeavour to review their universities’ specialty-specific medical education against reference objectives. Future curriculum development should target the elimination of identified gaps and evaluate the attainment of palliative care competencies by medical learners.